Uso de habitats artificiais no manejo e conservação de recursos pesqueiros em reservatórios. - Santos, Luciano Neves dos (2008)
Manipulation experiments of aquatic habitats were performed in two Brazilian reservoirs to investigate the potential of artificial structures in the management and conservation of fisheries resources. In Chapter I, six different types of habitats (rocks, logs, pipes, bushes, artificial macrophytes and structureless areas) in the Itaipu Reservoir, Paraná, were systematically surveyed by visual censuses and gillnets, with purpose to address the role of submerged habitat architecture in structuring fish assemblages based on the premises of habitat template theory. Despite some species were common to many different habitats, the functional attributes of species life history, which were compiled from published works, explained better the fish-habitat association patterns than the presence-absence data. Also, within the functional attributes, reproductive traits were better predictors than the trophic or morphological. In Chapter II, artificial reefs of same dimensions and complexity but of different materials (ceramic, concrete and PVC) were deployed in an area of the Itaipu Reservoir, aiming to investigate the effects of reef material and the successional mechanisms on fish colonization. Highest fish biomass, abundance and richness in the ceramic treatments appeared to be more related to high colonisation and species turnover rates than to species-specific size-effects. Also, temporal variations in life history traits of the fish composition indicate that sucessional mechanisms have modulated reef colonization. Finally, in Chapter III, natural and artificial rocky banks, located, respectively, in areas allowed and prohibited to fishing, were surveyed in Lajes Reservoir to evaluate the interactive effects of no-take reserves × invasive species on native fish assemblages. The native Cichlidae were affected by fishing and invasive species but the later masked the positive effects of fishing restriction measures. The overall results suggest that submerged habitat manipulation, through the use of artificial structures, is a promising tool to protect and manage the tropical fishes.